A wrinkle in time - L'Engle, Madeleine (New York Farrar, Straus, and Giroux, 1962)
Meg Murry and her friends become involved with unearthly strangers and a search for Meg's father, who has disappeared while engaged in secret work for the government.
Keywords: Science fiction